Potential association between COVID-19 and neurological disorders: analysis of common genes and therapeutics - Chen, Wenzhi; Jiang, Shishi; Li, Cheng; Li, Shu; Wang, Junling; Xu, Renshi (Frontiers in Neurology, 2024)
As the COVID-19 pandemic persists, the increasing evidences suggest that the patients with COVID-19 may face the risks of the neurological complications and sequelae. To address this issue, we conducted a comprehensive study aimed at exploring the relationship between COVID-19 and various neurological disorders, with a particular focus on the shared dysregulated genes and the potential therapeutic targets. We selected six neurological disorders for investigation, including Alzheimer's disease, epilepsy, stroke, Parkinson's disease, and the sleep disorders. Through the bioinformatics analysis of the association between these disorders and COVID-19, we aimed to uncover the common molecular mechanisms and the potential treatment pathways. In this study, we utilized the publicly available RNA-Seq and microarray datasets, and employed tools such as Limma and DESeq2 for the differential gene analysis. Through the Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis, we explored the common biological features and pathways. Additionally, we focused on analyzing the regulatory roles of miRNA and transcription factors on the shared differentially expressed genes, and predicted the potential drugs interacting with these genes. These analyses contribute to a better understanding of the relationship between COVID-19 and the neurological disorders, and provide a theoretical basis for the future treatment strategies. Through this research, we aim to offer the deeper insights to the scientific community and present the new perspectives for the clinical practice in addressing the challenges of the neurological complications and sequelae faced by the COVID-19 patients.